United Nations - African Union Cooperation In Conflict Prevention, Peacekeeping and Peacebuildin - L. I. Romadan; V. A. Shagalov (Vestnik MGIMO-Universiteta)
The article addresses the cooperation between the United Nations and regional organizations, in particular the African Union in the sphere of security and settlement of conflicts. Over the last decade the role of the AU and sub regional organizations has dramatically increased. Through its agencies of ensuring peace and security the African Union is making significant contribution to strengthening stability and promotion of democracy and human rights in Africa. In the beginning of the article authors make a review of the level of security on the African continent and stress the sharpest conflict zones. According to researches one of the most turbulent regions on continent in terms of security is the North-East Africa. Continuing quarter-century war in Somalia, conflict relations between Somalia and Ethiopia, the border crises between Ethiopia and Eritrea, which in the late 20th century turned into the war between the two countries, finally, the number of armed clashes in Sudan attracted the special attention to the region of the entire world community. Authors pay the main attention to the cooperation between the United Nations and the African Union in the sphere of settling regional conflicts and holding peacekeeping operations. In the article the main mechanisms and methods that are used by the United Nations and the African Union to hold peacekeeping operations are analyzed in details. The situation in Somalia and efforts of the United Nations and the African Union that are making towards stabilization in this country are also studied. Authors reveal the basic elements and make a review of the mixed multicomponent peacekeeping operation of the United Nations and the African Union in Sudan. In the conclusion authors stress the measures that could strengthen the strategic cooperation between the United Nations and the African union. According to the authors the most important task is to solve problems of financing joint peacekeeping operations quickly and effectively.